Primary Small Cell Carcinoma of the Vagina - Rafael Oliveira; Mayra Coelho Bócoli; João Carlos Saldanha; Eddie Fernando Candido Murta; Rosekeila Simões Nomelini (Case Reports in Obstetrics and Gynecology)
The primary small cell carcinoma of the vagina is rare, and it is a highly aggressive malignancy with no consensus regarding the treatment of this tumor. The survival rate for patients treated in the early stages is around two years. We related the case report of a patient of 41 years with a vegetative and necrotic lesion in left vaginal wall, in middle and upper third, and involvement of parametrium in its proximal third and medium third. A biopsy showed a small cell undifferentiated carcinoma composed of epithelial cells with round nuclei, oval or elongated, hyperchromatic nuclei, with little distinct nucleoli, and scarce cytoplasm. Immunohistochemistry showed positivity for AE1/AE3, CD57, and chromogranin A. The patient received 6 cycles of chemotherapy with cisplatin and etoposide and radiotherapy, achieving complete response, with complete regression of the lesion. The patient had no sign of tumor recurrence and locoregional or distant metastases after 5 months of followup.